2017
DOI: 10.1177/1060028017720946
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Vancomycin Associated With the Development of Nephrotoxicity in Patients With Class III Obesity

Abstract: Obesity and other factors are associated with a higher risk of vancomycin-associated nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…There have been studies on the risk factors for VA-AKI in the past [22][23][24]. Like previous studies, a positive correlation between VA-AKI and increasing vancomycin trough concentrations and baseline serum creatinine was found in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There have been studies on the risk factors for VA-AKI in the past [22][23][24]. Like previous studies, a positive correlation between VA-AKI and increasing vancomycin trough concentrations and baseline serum creatinine was found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we found age was correlated with VA-AKI, yet compared with new-borns and infants age group, older age group had less OR for development of VA-AKI. Concomitant administration of diuretics, PTZ and meropenem could increase the incidence of nephrotoxicity [22,26,27], except concomitant NSAIDs seems to have a protective role for VA-AKI. In each age group, VA-AKI incidence was lower in patients with concomitant NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggesting a causal relationship between doses and therapeutic targets of vancomycin and nephrotoxicity are conflicting and marked by confounding factors . Although there is minimal evidence supporting efficacy in maintaining therapeutic levels between 15 and 20 mg/L, several studies have evaluated the safety of this recommendation, comparing nephrotoxicity rates above and below 15 mg/L levels . A systematic review and a meta‐analysis conducted by van Hal et al included 15 studies in which trough serum levels of vancomycin ≥15 mg/L were associated with a higher risk of nephrotoxicity when compared to levels <15 mg/L (OR 2.67, P < 0.01).…”
Section: Vancomycinmentioning
confidence: 93%
“…The incidence of nephrotoxicity caused by vancomycin varies greatly among various studies, with rates as low as zero in the absence of other concomitant nephrotoxins, up to 40% in combination with other potentially nephrotoxic drugs, with a higher prevalence frequently described from 5% to 7%, involving different factors that may speed up or enhance the occurrence of nephrotoxicity, which may be related to the patient and/or the drug . Among the patient‐related factors, the most important are advanced age, reduced kidney function, dehydration, reduced renal mass, sex (women have lower muscle mass and body water quantity), obesity, hypoalbuminemia, and sepsis, while drug‐related risk factors include administration concomitant with other nephrotoxic drugs such as aminoglycosides, loop diuretics, amphotericin B, piperacillin‐tazobactam, acyclovir, vasopressors and intravenous contrast media; as well as long treatment duration and high serum dosage of this antimicrobial …”
Section: Vancomycinmentioning
confidence: 99%
See 1 more Smart Citation